2018
DOI: 10.1142/s0217595918400080
|View full text |Cite
|
Sign up to set email alerts
|

Coordinating Supply Chain with Buy-Back Contracts in the Presence of Risk Aversion

Abstract: This paper addresses the operational decisions and coordination of the supply chain in the presence of risk aversion, where the risk averse retailer’s performance is measured by a combination of the expected profit and conditional value-at-risk (CVaR). Such performance measure reflects the desire of the retailer to maximize the expected profit on one hand and to control the downside risk of the profit on the other hand. The impact of risk aversion on the supply chain’s decision and performance is also explored… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 30 publications
0
8
1
Order By: Relevance
“…For example, Zhang et al (2020b) examine the effect of risk aversion on the retailer's optimal order decision with backlogging. A buy-back contract was proposed by Luo et al (2018) to coordinate a supply chain consisting of a risk-neutral manufacturer and a risk-averse retailer.…”
Section: Supply Chain Decisions and Coordination With Risk Aversionmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, Zhang et al (2020b) examine the effect of risk aversion on the retailer's optimal order decision with backlogging. A buy-back contract was proposed by Luo et al (2018) to coordinate a supply chain consisting of a risk-neutral manufacturer and a risk-averse retailer.…”
Section: Supply Chain Decisions and Coordination With Risk Aversionmentioning
confidence: 99%
“…A buy‐back contract was proposed by Luo et al. (2018) to coordinate a supply chain consisting of a risk‐neutral manufacturer and a risk‐averse retailer.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Choi showed that the retailer's risk aversion behavior plays a key role in the optimal decision-making of each subject of the supply chain [38]. Luo proved that the risk-averse retailer in buyback contracts would reduce the order quantity, leading to the reduction of supply chain performance [39]. Xie analyzed the effect of decision-makers' risk attitude on different supply chain coordination contracts, and found that risk parameters played a key role in contract design [40].…”
Section: Risk Aversion In the Supply Chainmentioning
confidence: 99%
“…Xie et al [29] further extend their model by using mean-CVaR as the loss-averse retailer's criterion and investigate the supply chain coordination. Luo et al [30] use buyback contract to study the supply chain coordination under mean-CVaR criterion, and investigate the effect of allocation rule in the platform selling model.…”
Section: Literature Reviewmentioning
confidence: 99%